Kurikulum Merdeka Belajar Dalam pandangan Perspektif Tujuan Pendidikan Islam - Madaniyah, Madaniyah; Roza, Ellya (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this research is to analyze the Independent Learning Curriculum from the perspective of Islamic Education Objectives. This type of research is a literature review. Data collection with documentation. Data analysis with SLR. The results of the research are The Freedom to Learn Curriculum in the perspective of the goals of Islamic education outlines freedom to learn as the main foundation in achieving human perfection. The objectives of Islamic education included in the curriculum include the formation of noble morals, intellectual development, and mastery of knowledge that brings benefits to oneself and society. In addition, a holistic approach in teaching and learning is also emphasized, with an emphasis on integration between religious knowledge and general knowledge to create individuals who are balanced in spiritual, intellectual and social aspects. Thus, the Merdeka Belajar Curriculum in the perspective of the objectives of Islamic education seeks to create a generation that is empowered, moral and broad-minded in accordance with the principles of Islamic teachings.